The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1021/bi201623v
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Deoxyhemoglobin with the Cytoplasmic Domain of Murine Erythrocyte Band 3

Abstract: The partial pressure of oxygen constitutes an important factor in the regulation of human erythrocyte physiology, including control of cell volume, membrane structure, and glucose metabolism. Because band 3 is thought to be involved in all three processes and because binding of hemoglobin (Hb) to the cytoplasmic domain of band 3 (cdb3) is strongly oxygen-dependent, the possibility that the reversible association of deoxyhemoglobin (deoxyHb) with cdb3 might constitute an O 2 -dependent sensor that mediates O 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 58 publications
(132 reference statements)
1
29
1
Order By: Relevance
“…the major integral protein of erythrocytes membrane, plays a key role in the organization of membrane cytoskeleton as well as in anion transport (anion exchanger 1, AE1) [37]. It was shown that both in humans and mice the affinity of band 3 fragment with M r of 43 kDa (CDB3) for T-Hb is much higher than for oxygenated hemoglobin [38,39]. These data allowed researcher to assume that T-Hb/band3 interaction is crucial for triggering the downstream pO 2 -dependent signals including altered cytoskeleton assembly which role in the maintenance of erythrocyte membrane integrity is well-documented [40][41][42][43].…”
Section: Resultsmentioning
confidence: 99%
“…the major integral protein of erythrocytes membrane, plays a key role in the organization of membrane cytoskeleton as well as in anion transport (anion exchanger 1, AE1) [37]. It was shown that both in humans and mice the affinity of band 3 fragment with M r of 43 kDa (CDB3) for T-Hb is much higher than for oxygenated hemoglobin [38,39]. These data allowed researcher to assume that T-Hb/band3 interaction is crucial for triggering the downstream pO 2 -dependent signals including altered cytoskeleton assembly which role in the maintenance of erythrocyte membrane integrity is well-documented [40][41][42][43].…”
Section: Resultsmentioning
confidence: 99%
“…Band 3 phosphorylation then determines increased cytosol concentration of glyceraldehyde dehydrogenase, phosphofructokinase and aldolase (glycolitic enzymes anteriorly inactive and attached to cdb3) and enhanced glycolysis [75]. Band 3 phosphorylation is also determined by deoxyhemoglobin which through binding to cdb3 enhances glycolisis via the same mechanism described above [77]. Sepsis hypoxic status reduces drastically the hexose monophosphate pathway and further, NADPH concentration, which is vital in producing reductants in order to protect RBCs from oxidative damage [78,79].…”
Section: Sepsis Induces Rbc Membrane Pro Teins Alterations Band 3 Promentioning
confidence: 92%
“…Band 3 phosphorylation and dephosphorylation depends on several intraerytrocytic alterations: calcium concentration [75], oxidative damage on RBC membrane [76], low oxygen partial pressure leading to increased deoxyhemoglobin levels [77]. These alterations are already described in sepsis and can, in part, explain this phenomenon.…”
Section: Sepsis Induces Rbc Membrane Pro Teins Alterations Band 3 Promentioning
confidence: 96%
“…In a second transgenic mouse, the same human sequence was inserted into murine band 3, except the amino acids responsible for deoxyHb binding (residues 12-23) were deleted, allowing us to determine how the lack of a deoxyHb-band 3 affects O 2 regulation of RBC properties. In the present study, we introduced a third mutation into murine band 3 (deletion of residues 1-11) that endows band 3 with a significantly higher affinity for deoxyHb (33,35) (Fig. 1).…”
Section: Generation Of Transgenic Murine Erythrocytes With Altered Dementioning
confidence: 99%